Epidemiology and clinical significance of cervical erosion in women attending a family planning clinic. Issue 6115 (25th March 1978) - Goldacre, M J; Loudon, N; Watt, B; Grant, G; Loudon, J D; McPherson, K; Vessey, M P
Abstract : Women attending a family planning clinic were studied to determine the relation between cervical erosion and clinical and social characteristics. The appearance of the cervix was recorded without knowledge of the women's symptoms. The prevalence of erosion increased with parity but, when the effects of other factors were controlled, decreased in women aged 35 and over. Erosion was significantly more common in women taking the "pill" and less common in women using barrier methods of contraception than in others. There was considerable variation between doctors in the reporting of erosion. No association was found between erosion and postcoital bleeding, dyspareunia, backache, or dysuria. There was a significant but modest association between erosion and vaginal discharge and a suggestion that erosion may sometimes be associated with nocturia and frequency of micturition. Vaginal flora was similar in women with and without erosion. Cervical erosion should not be regarded as pathological in asymptomatic women, nor should it be assumed necessarily to be the cause of symptoms in women with genitourinary complaints.